Liturgy and Scripture in Dialogue in the Baptismal Feasts of the Episcopal Church - Charles Gerald Martin (Religions, 2025)
The liturgical reforms of the mid-twentieth century had major impacts on not only the forms of liturgies in the Western church but also on liturgical theology. The 1979 Book of Common Prayer of the Episcopal Church, the Anglican province in the United States, along with several dioceses across the world, represents the culmination of these developments in that jurisdiction. Among its revolutionary suggestions is the reservation of Holy Baptism for certain occasions: the Easter Vigil, Pentecost, All Saints’ Day or the Sunday following, the Feast of the Baptism of Our Lord, and the visitation of a bishop. Many liturgical guides emphasize the advantages of observing these so-called “baptismal feasts,” but none treat them in any lengthy manner. Do the different occasions for baptism have something specific to say about what baptism is? How do the appointed lectionary readings shed light on baptism, and vice versa? In this article, I will explore these feasts and especially their assigned lessons in the Revised Common Lectionary. I will show that when read with a liturgical hermeneutics, the appointed scriptures and, therefore, the baptismal feasts themselves paint a comprehensive picture of a contemporary baptismal theology.